2019
DOI: 10.1155/2019/9605980
|View full text |Cite
|
Sign up to set email alerts
|

Nerolidol Suppresses the Inflammatory Response during Lipopolysaccharide-Induced Acute Lung Injury via the Modulation of Antioxidant Enzymes and the AMPK/Nrf-2/HO-1 Pathway

Abstract: Acute lung injury (ALI) is a life-threatening disease that is characterised by the rapid onset of inflammatory responses. Lipopolysaccharide (LPS) is an endotoxin that plays an important role in triggering ALI via pneumonia and sepsis. However, no effective therapeutic strategies are currently available to treat ALI. Nerolidol is an aliphatic sesquiterpene alcohol that is found in the essential oils of many flowers as well as floral plants. It has been shown to exhibit anti-inflammatory, antioxidant, and antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…The dioscin treated mMECs for different time periods (0, 0.5, 1, 3, 6, and 12 h), and the results showed that dioscin increased the protein expression of total Nrf2 and nuclear Nrf2 and phosphorylation of AMPK and HO-1 (Figures 5(a) and 5(c) – 5(f) ), decreased the protein of Nrf2 in the cytoplasm, and reduced reactive oxygen (Figures 5(a) , 5(b) , and 5(g) ). Previous studies suggested that AMPK is an upstream of Nrf2 [ 34 ]. The results showed dioscin also promoted AMPK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…The dioscin treated mMECs for different time periods (0, 0.5, 1, 3, 6, and 12 h), and the results showed that dioscin increased the protein expression of total Nrf2 and nuclear Nrf2 and phosphorylation of AMPK and HO-1 (Figures 5(a) and 5(c) – 5(f) ), decreased the protein of Nrf2 in the cytoplasm, and reduced reactive oxygen (Figures 5(a) , 5(b) , and 5(g) ). Previous studies suggested that AMPK is an upstream of Nrf2 [ 34 ]. The results showed dioscin also promoted AMPK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…The content of intracellular ROS expression is regulated by at least two types of AOEs. The first type comprises enzymes are associated with ROS scavenger, containing superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase [ 3 , 4 ]. The second type comprises oxidative stress-induced enzyme, such as heme oxygenase-1 (HO-1) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first type comprises enzymes are associated with ROS scavenger, containing superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase [ 3 , 4 ]. The second type comprises oxidative stress-induced enzyme, such as heme oxygenase-1 (HO-1) [ 4 , 5 ]. Expression of SOD, GPx, catalase, and HO-1 is regulated by nuclear factor erythroid 2–related factor 2 (Nrf2), which is the transcription factor and downstream factor of 5’AMP-activated protein kinase-2 (AMPK2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, inhibiting inflammation is an important link for the prevention of ALI. Furthermore, previous reports have shown that ROS can produce lipid peroxidation by binding to polyunsaturated fatty acids in the cell membrane, resulting in producing highly cytotoxic malondialdehyde (MDA), which subsequently destroys the stability of the biofilm and increases its permeability, leading to cell damage or necrosis [16][17][18]. Both lipid peroxidation and excessive inflammation response caused by oxidative stress are important reasons of ALI, and the pathological changes of ALI are characterized by oxidative damage, excessive inflammation, and lipid peroxidation [19].The pathogenesis of and therapeutic drugs for ALI are have been the focus of current research for 30 years [20][21][22][23][24].…”
mentioning
confidence: 99%